1999
DOI: 10.1289/ehp.99107693
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of rat lung tumors from lifetime inhalation of diesel exhaust.

Abstract: Estimating the carcinogenic potential of exposure to diesel-engine ehaust particulates (DEPs) is problematic. In rats, high concentrations of DEPs (> 1,000 pg/m3) inhaled over a lifetime result in excess lung tumors. However, data for rats exposed to DEP at concentrtion not associated with lung overload are consistent with no tumorigenic effect Individual rat studies have only a limited number of exposure groups; therefore, we combined the tumor data from eight chronic inhalation studies in a meta-analysis. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Epidemiological data on workers exposed to such intensity levels of DE exposure are missing. It is known from animal studies that the lung cancer risk in rats can be described by a threshold model (Valberg & Crouch 1999). Following these calculations, the threshold can be expected between 160 and 600 lg/m 3 average continuous lifetime exposure.…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…Epidemiological data on workers exposed to such intensity levels of DE exposure are missing. It is known from animal studies that the lung cancer risk in rats can be described by a threshold model (Valberg & Crouch 1999). Following these calculations, the threshold can be expected between 160 and 600 lg/m 3 average continuous lifetime exposure.…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…Interestingly, some of these compounds induce skin irritation or sensitization (e.g., dimethylbenz[a]anthracene, 4,4´-methylenedianiline, and TCDD). Relevant to this relationship are the associations of DEPs with augmented sensitization and airway responsiveness (32,34-40) and possibly lung tumors, noted only in rats (322)(323)(324)(325)(326)(327)(328)(329)(330)(331)(332). In addition, toluene diamine is a metabolite of toluene diisocyanate (307), a potent asthmagen, and thereby links, in principal, reactive intermediates of carcinogens with asthma.…”
Section: Evaluating Human Exposure and Its Relationship To Asthmamentioning
confidence: 99%
“…Additionally, animal studies have shown that prolonged exposure of rats to high concentrations of diesel PM (>1 mg/m 3 ) initiated a dose-dependent progression of cellular changes that eventually led toward the development of benign and malicious lung tumours (Valberg and Crouch 1999).…”
Section: Introductionmentioning
confidence: 99%